Estados emocionales agudos en pobladores mexicanos durante la pandemia de COVID-19 - Plascencia De la Torre, Juan Carlos (2022)
The purpose of the study was to evaluate acute emotional states in Mexicans during the Covid-19 pandemic. Non-experimental-cross-sectional design. 585 Mexicans between 18 and 67 years of age participated. The DASS-21 scale was used to measure the variables of stress, anxiety and depression; and a questionnaire on situations related to confinement by COVID-19. The results show that a small percentage of the sample manifested negative emotional symptoms ranging from severe to very severe, as well as fear and anguish of contagion from a relative. Similarly, significant differences were identified between men and women, and age groups. The findings show the importance of designing and implementing psychological interventions aimed at reducing negative emotions during the coronavirus pandemic.